PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL ( Studi pada Badan Perencanaan Pembangunan Daerah Kabupaten Rembang ) - Rozak, Hasan Abdul; Fu’adi, Mukhammad Anwar (Jurnal Ilmiah Telaah Manajemen, 2016)
The purpose of this study is to analyze the effects of individual characteristics, job characteristics and compensation on the job performance with organizational commitment as mediator in Rembang Regional Development Planning Agency. This study use cencuss methode for collecting data, using statistical tests that include validity test with factor analysis, reliability test using Cronbach's alpha, double regression analysis, and significance test using the coefficient of determination to prove the validity of hypothesis and for mediation tests. The results of this study proved that model’s ability to correctly describe that the influence of individual characteristic, job characteristic, compensation and organizational commitment is 11,9% on job performance, and organizational commitment didn’t to mediating the influence of independence variable to dependence variabel. Keywords : individual characteristics, job characteristics, compensation, organizational commitment, job performance